Backup agreement as a coordination mechanism in a decentralized fruit chain in a developing country - Margy Nathalia Rojas Palacios; Diego León Pe\~na Orozco; Jesus Gonzalez-Feliu (Games, 2022)
This paper aims to analyze the impacts of a backup agreement contract on the performance of a small agricultural producers' citrus supply chain. A backup agreement contract, which ensures for each echelon that a quantity of products will be bought independently of real demand, is proposed to coordinate a three-echelon supply chain, aimed at improving income. After presenting an overview of the literature that shows various coordination mechanisms but no backup agreement proposals for supply chain coordination, this paper develops a decentralized three-echelon supply chain facing stochastic customer demand and includes the backup agreement as a coordination mechanism to guarantee a balanced relationship between the chain members. The model is tested in a real case study in Colombia, and a sensitivity analysis is provided. Results show that a backup agreement contract coordinates the small agricultural producers' supply chain and improves income for each echelon, especially for the small producer. However, the economic mechanism complexity can limit coordination among echelons, mainly because of a lack of trust and consolidated supply capacity from small farmers. The foregoing requires the development of an associative structure by small producers, which is proposed as future research work.
Keywords: 330; backup agreement; coordination; decentralization; small producer networks; supply chain